THE ETHICS OF ECSTASY: Georges Bataille and Amy Hollywood on Mysticism, Morality, and Violence - Bush, Stephen S. 1974- (2011)
Georges Bataille agrees with numerous Christian mystics that there is ethical and religious value in meditating upon, and having ecstatic episodes in response to, imagery of violent death. For Christians, the crucified Christ is the focus of contemplative efforts. Bataille employs photographic imagery of a more-recent victim of torture and execution. In this essay, while engaging with Amy Hollywood's interpretation of Bataille in Sensible Ecstasy, I show that, unlike the Christian mystics who influence him, Bataille strives to divorce himself from any moral authority external to the ecstatic episode itself. I argue that in his attempt to remove external authority he abandons the only resources that could possibly protect his mystical contemplation from engendering sadistic attitudes.
Keywords: Psychoanalysis; Ecstasy; Torture; Mysticism; Bataille